Interdisciplinary Distance Learning Workshop for IT Students - I. A. Andrianov; S. A. Rzheutskaya; M. V. Kharina (Открытое образование (Москва))
Purpose of research. The purpose of research is to present proposals for the development and use of technologies for automatic checking of problem solutions in the process of forming professional competencies of students of IT-directions in the information educational environment. The article analyzes the authors’ experience gained during the development and operation of a distance learning workshop for IT students, which implements the functions of automatic checking of problem solutions in various specialized disciplines. This approach made it possible to increase the effectiveness of teaching both in the process of classroom studies and in the organization of independent work of students.Methods and materials. The article presents the key points of the creation and development of the distance learning workshop, justifies its concept, according to which the learning workshop is an interdisciplinary resource, in which the function of automatic checking of problem solutions is subordinate to the main function of developing and consolidating the skills and abilities of an IT specialist. An approach to organizing automatic checking by testing the program code developed by a student in the process of solving an educational problem is presented, and an extension of this approach is proposed for organizing automatic checking in cases where the solution is not the program code, but, for example, a diagram, model or text document designed in accordance with the regulated rules. The architectural solution and some features of the implementation of the distance learning workshop are justified, its role in the educational process is determined. Results. The results of the use of the learning workshop in the process of teaching various courses are presented. The results of training in programming are the most significant, since this resource has been used for more than 15 years – during this time, extensive experience has been accumulated in its use, the results of training have been analyzed, and some problems have been identified and solved. An example of using the learning workshop in the course “Mathematical Logic and Theory of Algorithms” is presented, in which the implementation of automatic checking of problem solutions required non-standard solutions to refine the learning workshop. An additional useful function of the learning workshop as the means of developing English-language competence is presented.Conclusion. The results of the study show that the technologies of automatic checking of problem solutions and software based on them are an effective way to develop the professional skills of students of IT areas. Surveys of employers of graduates of IT areas allow us to conclude that there is a relationship between the results of students’ work recorded in a distance learning workshop during training, and their success in professional activities after graduation. Many of the graduates continue to use the learning workshop to further develop and train their professional skills – the resource is open.